2021
DOI: 10.1038/s41598-021-98878-w
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 first wave impact in the acute inflammatory surgical pathologies

Abstract: Anecdotal evidence suggests that community infection control measures during the COVID-19 outbreak have modified the number and natural history of acute surgical inflammatory processes (ASIP—appendicitis, cholecystitis, diverticulitis and perianal abscesses) admissions. This study aims to evaluate the impact of the COVID-19 pandemic on the presentation and treatment ASIP and quantify the effect of COVID-19 infection on the outcomes of ASIP patients. This was a multicentre, comparative study, whereby ASIP cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Farber et al ( 23 ) reported similar results regarding median hospital LOS in surgically managed patients between the two periods. Finally, Guadalajara et al ( 16 ) found a prolonged LOS in 2020 (6 days) compared to 2019 and 2021 (4 days both). This observation can be explained by the selection of conservative treatment and the fewer laparoscopy rates during the first wave of the pandemic, which can be attributed to concerns about the transmission of the virus with aerosolization.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Farber et al ( 23 ) reported similar results regarding median hospital LOS in surgically managed patients between the two periods. Finally, Guadalajara et al ( 16 ) found a prolonged LOS in 2020 (6 days) compared to 2019 and 2021 (4 days both). This observation can be explained by the selection of conservative treatment and the fewer laparoscopy rates during the first wave of the pandemic, which can be attributed to concerns about the transmission of the virus with aerosolization.…”
Section: Resultsmentioning
confidence: 93%
“…The mild complication rate (CDI or CDII) was similarly higher in the pandemic period ( 11 ). Finally, Guadalajara et al ( 16 ) reported increased complication rates of any Clavien-Dindo grade during 2020 compared both to 2019 and 2021. The difference between 2020 and 2021 is statistically significant ( p = 0.026).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In Ontario, patients with prior COVID-19 infection had a lower risk of multiple common surgeries [ 52 ]. An assessment of 10 hospitals in Spain revealed decreased laparoscopic approaches and longer stays, indicating that the standards had suffered [ 53 ]. Studies have also projected increased costs due to surgical delays [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the first wave of the SARS-CoV-2 pandemic, drastic restructuring of surgical services was applied, as part of a larger scheme aiming to protect health systems from being overwhelmed during the pandemic 1 , 2 . As a result of reserving resources to cope with the expected influx of patients with COVID-19, elective activity was postponed and acute surgical cases were treated preferably in an ambulatory rather than an inpatient setting 3–5 .…”
mentioning
confidence: 99%